AMPs inhibit the proliferation, migration, and invasion of lung cancer via the CHRM3/PI3K/AKT and CHRM3/MAPK pathways - Jun Wu; Congcong Huang; Shangning Wang; Liuyan Chen; Quan Cheng; Shao Zhang (Frontiers in Oncology)
AimsOur previous studies indicated that the overexpression of M3 muscarinic receptor (M3R/CHRM3) is related to a poor prognosis in patients with lung cancer and that Armillaria mellea polysaccharides (AMPs) can exhibit strong anticancer activity in vitro via apoptosis-related mechanisms in lung cancer cells. This study investigated whether AMPs exert anticancer activity through the CHRM3 signaling pathway.Materials and methodsLung cancer cell lines (A549, NCI-H1299, and NCI-H520) with stable overexpression or knockdown of CHRM3 were established by infection with recombinant lentivirus and selected under puromycin for one month. Stable cells were treated with or without 100 μg/mL AMPs for 24 h or 48 h. The changes in CHRM3 expression, cell proliferation, migration, and invasion were determined. The expression levels of phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT) and mitogen-activated protein kinase (MAPK) pathway-related proteins were detected. The antitumor activity of AMPs was further assessed in a xenograft mouse model bearing A549 cells with stable CHRM3 knockdown.ResultsCHRM3 was highly expressed in NCI-H520 cells and moderately expressed in A549 and NCI-H1299 cells. CHRM3 overexpression significantly increased while CHRM3 knockdown significantly decreased the cell proliferation, migration, and invasion. AMP treatment downregulated the expression of CHRM3 and decreased the cell proliferation, migration, and invasion. Moreover, CHRM3 overexpression significantly activated the PI3K/AKT and MAPK signaling pathways, whereas AMP treatment decreased CHRM3-induced PI3K/AKT and MAPK activation. In xenograft mice bearing A549 tumors, CHRM3 knockdown showed little inhibition on tumor growth, but AMP treatment inhibited the tumor growth.ConclusionAMP treatment inhibits the proliferation, migration, and invasion of lung cancer via the CHRM3/PI3K/AKT and CHRM3/MAPK pathways, thus exerting antitumor activity.